THE TEACHER CANDIDATES’ PERCEPTION ON TEACHING ENGLISH TO YOUNG LEARNERS: PERSEPSI CALON GURU DALAM MENGAJAR BAHASA INGGRIS UNTUK ANAK USIA MUDA - AFRIZANUR ASWAD; Kiagus Baluqiah (Teaching English and Language Learning English Journal, 2025)
This study aims to determine the perception of prospective teachers about how important it is to teach English to children at an early age or golden age. Researchers used quantitative descriptive methods. The subjects of this study were students from sixth semester who were taking English for Young Leaners courses in the English Language Study program at the University of Muhammadiyah Bengkulu who were referred to as teacher candidates. Data samples were taken from 42 active students. Researchers used questionnaires and interviews as instruments in this study. Using questionnaires to collect data from prospective teachers (frankel & wallen, 2009:395). The questions in the questionnaire were adapted from Supriyanti's theory (2012). This study resulted in a positive response from prospective teachers with a percentage of 95.24% neutral response and 2.78% negative response. The interview results of prospective teachers revealed the perception of prospective teachers that English for young learners is very important to learn when they are in their golden age easier to improve students ' new vocabulary in learning English, helping them communicate well in the era of globalization Around the world using English in communication. Keywords: Perception, Prospective teacher, English Young Learner